Kesenjangan sosial dan diskriminasi penduduk campuran (Mestizos) di Hindia Belanda dalam kurun abad 18-19 - Moch. Dimas Galuh Mahardika; Muhammad Yusuf Efendi (Historiography: Journal of Indonesian History and Education, 2022)
When the Dutch came to power in the East Indies Islands, indo-Europeans or mestizo or "anak kolong" were considered a bad image for Europeans. They were born as a result of marital relations between European men and bumiputra women. Europeans think that the mistresses (nyai) are guilty of the birth of Indo-European children. Though the combination of two cultures that enter the life of the community makes them accustomed to coexistence between the two. Classification in colonial societies made the difference even more pronounced, indo-Europeans increasingly marginalized by social gap and discrimination. Discriminatory policies that put Europeans first in terms of jobs, education, create resentment and frustration among Indo-Europeans. Those who are increasingly depressed due to the difficulty of living in the Dutch East Indies take shortcuts by committing criminal acts such as opium smuggling, theft, and prostitution. This article written with historiographical methods attempts to recount the lives of mixed-blooded populations as one of the contributions of the field of social history studies. This presentation is expected to be an alternative to historical discussions that may not be written much in the official historical narrative.Saat Belanda berkuasa di Kepulauan Hindia Timur, orang-orang Indoeropa atau mestizo atau anak kolong dianggap sebagai citra buruk bagi kalangan orang-orang Eropa. Mereka lahir akibat hubungan perkawinan/pergundikan antara lelaki Eropa dan perempuan bumiputra. Orang-orang Eropa beranggapan bahwa para gundik (nyai) bersalah atas kelahiran anak Indoeropa. Padahal perpaduan dua budaya yang masuk dalam kehidupan masyarakat membuat mereka terbiasa hidup berdampingan di antara keduanya. Klasifikasi dalam masyarakat kolonial membuat perbedaan semakin terasa, orang-orang Indoeropa semakin terpinggirkan dengan adanya kesenjangan sosial dan diskriminasi. Kebijakan diskriminatif yang mengutamakan orang-orang Eropa dalam hal pekerjaan, pendidikan, menciptakan rasa dendam dan ketidaknyamanan di kalangan orang-orang Indoeropa. Perempuan yang semakin tertekan akibat sulitnya kesempatan hidup di Hindia Belanda mengambil jalan pintas dengan melakukan tindakan kriminal seperti penyelundupan opium, pencurian, dan prostitusi. Artikel yang ditulis dengan metode historiografi ini mencoba untuk menceritakan kehidupan penduduk berdarah campuran sebagai salah satu kontribusi bidang kajian sejarah sosial. Pemaparan ini diharapkan dapat menjadi alternatif diskusi sejarah yang mungkin belum banyak ditulis di dalam narasi sejarah resmi.